أثر محددات الجودة المؤسساتية على الابتكار في الدول العربية: دراسة تجريبية - شوقي, شادلي; عباده, عبد الرؤوف; حميدات, عمر (جامعة الوادي - University of Eloued, 2022)
الهدف من هذه الدراسة هو اختبار تأثير محددات الجودة المؤسساتية:(حرية التعبير والمساءلة، الاستقرار السياسي وغياب العنف، فعالية الحكومة، الجودة التنظيمية، سيادة القانون، مراقبة الفساد.) على الابتكار في الدول العربية خلال الفترة من 2011 إلى غاية 2019،باستخدام بيانات 11 دولة.وذلك بتقدير النماذج الثلاثة للسلاسل الزمنية المقطعية: النموذج الانحدار التجميعي، نموذج التأثيرات الثابتة، ونموذج التأثيرات العشوائية، وبعد إجراء اختبارات المفاضلة أظهرت النتائج: أن نموذج التأثيرات العشوائية هو الملائم، وأن الابتكار يتأثر بالجودة التنظيمية و مراقبة الفساد بشكل سلبي، كما تبين أيضا أن الابتكار لا يتأثر بحرية التعبير والمساءلة،الاستقرار السياسي وغياب العنف،فعالية الحكومة، سيادة القانون. The aim of this study is to test the effect of the institutional quality determinants: (voice and accountability, political stability and absence of violence, government effectiveness, regulatory quality, rule of law, control of corruption) on the innovation in the Arab countries during the period from 2011 to 2019. To doing so, this paper uses the data of 11 Arab countries through estimation and comparison between the Panel Data models: pooled regression model, fixed effects model, and the random effects model. The results show that the random effects model is appropriate, and regulatory quality and control of corruption negatively affecte the Innovation, the result also found that innovation is not affected by voice and accountability, political stability and absence of violence, government effectiveness and rule of law
مقال
Keywords: جودة مؤسساتية ; ابتكار ; نموذج بيانات سلاسل زمنية مقطعية